Manajemen Unit Bahasa Asing (UNIBA) Dalam Meningkatkan Kemampuan Bahasa Asing Santri di Pesantren Modern Al-Junaidiyah Biru Bone - Fitriani Fitriani; Hasbullah Hasbullah (Institusi Agama Islam Negeri (IAIN) Bone, 2023)
This research was conducted at Pesantren Modern Al-Junaidiyah Biru Bone which aims to find out how the management of foreign language units (UNIBA) students and students' foreign language skills at Pesantren Modern Al-Junaidiyah Biru Bone. The type of research used is qualitative research, using a management approach and a pedagogic approach. In data collection using observation, interview and documentation methods. Then the data obtained is analyzed in three stages, namely the data reduction stage, data presentation (display data), and conclusion drawing and verification. The results showed that with the implementation of good management will be able to improve the foreign language skills of students at Al-Junaidiyah Biru Bone Modern Boarding School.